2022
DOI: 10.1111/phpp.12776
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection by clothing: A review

Abstract: Clothing is a mainstay of photoprotection and is commonly assessed by an ultraviolet protective factor (UPF) rating. We present original data on the increasing interest in photoprotective clothing as assessed by Google Trends and the frequency of UPF-rated clothing among a sample of Fortune 1000 companies. We review photoprotective clothing and occupational health, international standards governing UPF ratings, parameters of fabrics guiding UPF in clothing, synthetic and naturally occurring materials being exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Soto et al 16 compared the photoprotective behaviors of patients before and after being diagnosed with melanoma and found that clothing was one of the least used photoprotection measures before diagnosis, and Aleisa et al 17 reported that this measure was less used than other photoprotection measures after diagnosis of melanoma. The use of clothing for photoprotection is increasing 18 . Lycra and elastane fabrics can both have an ultraviolet protection factor >50, although cotton clothing can also provide adequate photoprotection 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soto et al 16 compared the photoprotective behaviors of patients before and after being diagnosed with melanoma and found that clothing was one of the least used photoprotection measures before diagnosis, and Aleisa et al 17 reported that this measure was less used than other photoprotection measures after diagnosis of melanoma. The use of clothing for photoprotection is increasing 18 . Lycra and elastane fabrics can both have an ultraviolet protection factor >50, although cotton clothing can also provide adequate photoprotection 19 …”
Section: Discussionmentioning
confidence: 99%
“…The use of clothing for photoprotection is increasing. 18 Lycra and elastane fabrics can both have an ultraviolet protection factor >50, although cotton clothing can also provide adequate photoprotection. 19 Our findings indicate that the use of photoprotection measures was lowest in patients with melanoma, except sunscreen and sunglasses, which were used less by SCC patients than any other group.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Furthermore, SPF 100+ sunscreen (infrared covered) was introduced into the daily care of all participants and reapplied every 6 h to prevent photoaging and photo-induced inflammation in erythematous areas [17][18][19][20][21][22]. The sunscreen was applied in photo-exposed areas during the whole duration of the study, and during the summer all participants wore UVB protective clothes [23][24][25].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…UV protective clothing is increasing in popularity in recent years with more consumers seeking options [6].…”
Section: Introductionmentioning
confidence: 99%
“…UV protective clothing is increasing in popularity in recent years with more consumers seeking options [ 6 ]. Although intuitively, most fabrics will offer some degree of UV protection by creating a physical barrier between the skin and UV sources, such as the sun, UV protective clothing is rated based on testing for the amount of UV-A and UV-B blockage provided by the textile.…”
Section: Introductionmentioning
confidence: 99%